A cultura Kaingang como expressão geográfica da territorialidade e da educação indígena no município de Charrua - RS - Enge, Tiara Rubia (2010)
This work has for main objective to analyze as it occurs the territoriality and the indigenous education kaingang in the Ligeiro Indigenal Reserve, in Charrua-RS. Search to understand the reserve as ethnic domain, under looking at of the indigenous education not-deed of division in order to identify to the different relations constructed in the indigenous territory kaingang. Also it verifies as if operationalize the definition of this territory and how much this contributes in the partner-cultural organization of kaingang. The method dialetic/inductive is used as main. Finally, on aspects are characterized the material and incorporeal culture searching to value the indigenous education kaingang permeating the quarrel on the inclusion of the indigenous territoriality as made element of the Charrua-RS.